Adherencia terapeutica y su incidencia en la capacidad de resiliencia ante enfermedad catastrofica en un paciente de 68 años de edad del Centro de Hemodialisis San Rafael, cantón Rumiñahui - Ordóñez Puca, José Mauricio (2021)
This case study was carried out with the objective of determining the factors in therapeutic adherence and its incidence in the resilience capacity to catastrophic disease in a 68-year-old patient, from the “San Rafael” hemodialysis center, Cantón Rumiñahui, Pichincha , where the catastrophic disease is kidney failure, the patient was approached to fill out the respective clinical history and personal data that the center requires as a new admission, in addition, psychometric batteries were applied such as the HAMILTON test of Anxiety, BECK of Depression and Minimental, additionally, their mood was evaluated with the Rosemberg self-esteem scale test. With the information obtained and the results of the respective tests, we proceeded to develop a therapeutic plan using the Cognitive Behavioral Therapy (CBT) approach, which seeks to replace the thoughts that the patient has about little worth and limitations due to their condition. that overwhelm him, accompanied by depression and anxiety, in addition, emphasis will also be placed on the resilience process and how to properly handle adverse situations based on the fact that thoughts originate emotions, then the patient's cognitions will be examined, you will evaluate them and question negative beliefs to replace them with more appropriate beliefs.